Paranoid Schizophrenia is Characterized by Increased CB(1) Receptor Binding in the Dorsolateral Prefrontal Cortex - Dalton, Victoria S (Nature Publishing Group, 2011)
A number of studies suggest a dysregulation of the endogenous cannabinoid system in schizophrenia (SCZ). In the present study, we examined cannabinoid CB(1) receptor (CB(1)R) binding and mRNA expression in the dorsolateral prefrontal cortex (DLPFC) (Brodmann's area 46) of SCZ patients and controls, post-mortem. Receptor density was investigated using autoradiography with the CB(1)R ligand [(3)H] CP 55 940 and CB(1)R mRNA expression was measured using quantitative RT-PCR in a cohort of 16 patients with paranoid SCZ, 21 patients with non-paranoid SCZ and 37 controls matched for age, post-mortem interval and pH. All cases were obtained from the University of Sydney Tissue Resource Centre. Results were analyzed using one-way analysis of variance (ANOVA) and post hoc Bonferroni tests and with analysis of covariance (ANCOVA) to control for demographic factors that would potentially influence CB(1)R expression. There was a main effect of diagnosis on [(3)H] CP 55 940 binding quantified across all layers of the DLPFC (F(2,71)=3.740, p=0.029). Post hoc tests indicated that this main effect was due to patients with paranoid SCZ having 22% higher levels of CB(1)R binding compared with the control group. When ANCOVA was employed, this effect was strengthened (F(2,67)=6.048, p=0.004) with paranoid SCZ patients differing significantly from the control (p=0.004) and from the non-paranoid group (p=0.016). In contrast, no significant differences were observed in mRNA expression between the different disease subtypes and the control group. Our findings confirm the existence of a CB(1)R dysregulation in SCZ and underline the need for further investigation of the role of this receptor particularly in those diagnosed with paranoid SCZ.